2004
DOI: 10.1177/0363546503261717
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Tibial Inlay versus Transtibial Techniques for Posterior Cruciate Ligament Reconstruction

Abstract: The study suggests that either technique may be performed with similar biomechanical results at initial fixation under these loading conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 28 publications
3
47
1
1
Order By: Relevance
“…Applying 1,000 cycles of posterior load of 100-N in this study resulted in no graft rupture at the killer turn in the BTB-tunnel and no significant difference in PTT as well as laxity increase between the BTB-tunnel and the BTB-inlay. These findings are in accordance with previous studies [12,14]. According to the literature on the cyclic loading tests to the PCL reconstructed-knee, a load of 300-N represents a load level during an aggressive rehabilitation program, and a load of 89-N simulates mechanical conditions during continuous passive knee motion [15].…”
Section: Discussionsupporting
confidence: 92%
“…Applying 1,000 cycles of posterior load of 100-N in this study resulted in no graft rupture at the killer turn in the BTB-tunnel and no significant difference in PTT as well as laxity increase between the BTB-tunnel and the BTB-inlay. These findings are in accordance with previous studies [12,14]. According to the literature on the cyclic loading tests to the PCL reconstructed-knee, a load of 300-N represents a load level during an aggressive rehabilitation program, and a load of 89-N simulates mechanical conditions during continuous passive knee motion [15].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have reported the transverse lengths at the femoral insertion, central portion and tibial insertion levels (Triantafyllidi et al;Fanelli et al;Sheps et al, 2005;Margheritini et al, 2004;Cosgarea & Jay, 2001;Stähelin et al, 2001). Harner et al (1999) discovered that the AL fascicle is greater than the PM, which differs from data reported by Takahashi The most relevant finding of this study was that the PCL did not have the same dimension for the entirety of its length, replicating the "sand clock" form with wide bases and a thin center, particularly in its anteroposterior length.…”
Section: Discussioncontrasting
confidence: 81%
“…Despite the technique used, current PCL reconstruction methods do not consistently restore posterior tibial translation to that of the contralateral knee [4,17,34]. Residual increased posterior translation of the tibia has been documented after traditional transtibial techniques [11,17,22,28], and postoperative stability of the knee and subjective patient outcomes are not improved after alternative approaches such as tibial inlay fixation techniques [14,18,19,21,24,31] or double-bundle reconstruction of the PCL [1,2,8,10,35].…”
Section: Introductionmentioning
confidence: 99%